Overrun causations under advance payment regimes - Aje, O.; Olatunji, Oluwole; Olalusi, O. (Emerald Group Publishing, 2017)
Purpose: Evidence suggests project owners could use advance payments to prevent cost escalations. The purpose of this paper is to elicit the relationships between causations of overruns when advance payments are issued to contractors. Design/methodology/approach: In total, 97 responses from a questionnaire survey were analysed. Additional data on 51 projects, completed between 2000 and 2014 under different advance payments regimes, were also obtained and analysed. Findings: Project owners issue advance payments to contractors so as to avoid delays. However, statistical correlation between advance payments and overrun causations are not significant. Although cost overruns were higher in large projects than in small projects, schedule overruns were more in small projects than in large projects. Schedule overruns were caused most significantly by contractors’ site management approaches. Design and documentation issues were identified as the most prevalent cause of cost overruns. Regression models are proposed to elicit overruns when advance payments are issued. Practical implications: Extant debates on project overruns in construction and project management literature are robust. Nonetheless, the study elicits considerable knowledge gaps regarding the roles of advance payments in fostering project performance. Originality/value: This pioneering work indexes the relationship between advance payment and project overruns in Nigeria. It is also the first attempt to document the probability distribution of overruns in Nigeria, particularly under specific advance payment regimes.